The Economics of Transboundary River Management - Erik Ansink; Harold Houba (Tinbergen Institute, 2014)
We survey the economics of transboundary river water allocation, which emerged in the 1960s and has matured over the last decade due to increasing concerns over water scarcity and pollution. We outline the major approaches and pay specific attention to the strategic aspects of transboundary river water allocation. These strategic aspects are captured by employing game theory to assess the economics of transboundary river water allocation in a simple model of river sharing. This model allows us to show how conflict and cooperation over transboundary water resources may occur. It also allows us to pay specific attention to the efficiency, sustainability, and fairness of solutions to this model. We compare and contrast both cooperative and non-cooperative approaches and we relate their solutions to illustrative examples.
Keywords: C71; C73; D63; D74; F53; Q25; 330; River sharing problem; River claims problem; Fairness; Efficiency; Sustainability; Water allocation agreement; Bargaining; Water trade; Sharing rules; Axiomatic approach